An Activist Approach to Sport Meets Youth From Socially Vulnerable Backgrounds: Possible Learning Aspirations. Issue 1 (2nd January 2017) - Luguetti, Carla; Oliver, Kimberly L.; Dantas, Luiz Eduardo Pinto Basto Tourinho; Kirk, David
Abstract : Purpose: This study was a 2-phase activist research project aimed at co-creating a prototype pedagogical model for working with youth from socially vulnerable backgrounds in a sport context. This article addresses the learning aspirations (learning outcomes) that emerged when we created spaces for youth to develop strategies to manage the risks they face in their community.Method: This study took place in a socially and economically disadvantaged neighborhood in a Brazilian city where we worked with a group of 17 boys aged 13 to 15 years old, 4 coaches, a pedagogic coordinator, and a social worker. During a 6-month period, we collected multiple sources of data including field journal entries/observations (38) and audio records of youth work sessions (18), coaches' work sessions (16), combined coaches and youth work sessions (3), and meetings between the lead and the 2nd author for debriefing and planning sessions (36).Results: By using an activist approach, 4 learning aspirations emerged: becoming responsible/committed, learning from mistakes, valuing each other's knowledge, and communicating with others.Conclusion: Findings suggest there is a need for more sports programs that start from young people's concrete needs and life situations and look to create places for youth to see alternative possibilities and take action.